The fault in our stars - Green, John; Burke, Kelly (Royal National Institute for the Blind London, 2013)
Despite the tumour-shrinking medical miracle that has bought her a few years, Hazel has never been anything but terminal, her final chapter inscribed upon diagnosis. But when a gorgeous plot twist named Augustus Waters suddenly appears at Cancer Kid Support Group, Hazel's story is about to be completely rewritten